Toxicity of anacardium occidentale shoots (pucuk gajus) extract on zebrafish embryos - Haron, Normah; Tajuddin, Nurul Natasyah; Abdul Wahab, Widya; Mohd Nasir, Mohd Hamzah; Assia, Sassi; Mat Jusoh, Hanapi (IIUM Press, 2023)
The use of various medicinal plant to remedy specific disease has become more popular and grown intensively due to the preference for using medicinal plant instead of synthetic drugs. However, it is vital to know the safe dose limit of natural products consumption. In this present study, the medicinal plant such as Anacardium occidentale (cashew) shoots which is commonly consumed as ulam or as a salad in some Asian countries such as Malaysia and Indonesia was used. This study aims to evaluate the antioxidant capacity of the cashew shoots by using 70% methanolic:water and to determine its toxicity effect on the Danio rerio (zebrafish) embryos. The antioxidant capacity was calculated in IC50 value where the A. occidentale methanolic extract was found to have higher antioxidant activity (IC50 = 4.02 ± 0.02 μg/mL) as compared to ascorbic acid (7.44 ± 0.02 μg/mL) (p<0.05). At higher concentration of A. occidentale (9.802 μg/mL), it showed the toxicity effects on the mortality, hatchability, and several deformations (spinal curve, heart complication, and the presence of oedema). Therefore, it is recommended to use lower concentration of extract to prevent toxicity.